How to measure wisdom: content, reliability, and validity of five measures - Glück, Judith; König, Susanne; Naschenweng, Katja; Redzanowski, Uwe; Dorner-Hörig, Lara; Strasser, Irene; Wiedermann, Wolfgang (Frontiers in Psychology, 2013)
Wisdom is a field of growing interest both inside and outside academic psychology, and researchers are increasingly interested in using measures of wisdom in their work. However, wisdom is a highly complex construct, and its various operationalizations are based on quite different definitions. Which measure a researcher chooses for a particular research project may have a strong influence on the results. This study compares four well-established measures of wisdom—the Self-Assessed Wisdom Scale (Webster, 2003, 2007), the Three-Dimensional Wisdom Scale (Ardelt, 2003), the Adult Self-Transcendence Inventory (Levenson et al., 2005), and the Berlin Wisdom Paradigm (Baltes and Smith, 1990; Baltes and Staudinger, 2000)—with respect to content, reliability, factorial structure, and construct validity (relationships to wisdom nomination, interview-based wisdom ratings, and correlates of wisdom). The sample consisted of 47 wisdom nominees and 123 control participants. While none of the measures performed “better” than the others by absolute standards, recommendations are given for researchers to select the most suitable measure for their substantive interests. In addition, a “Brief Wisdom Screening Scale” is introduced that contains those 20 items from the three self-report scales that were most highly correlated with the common factor across the scales.